Enhancing Family Food Security Through Experiential Learning-Based Training In Organic Food Cultivation - Sarah, Sarah; Nurhayati, Sri (Jurnal Simki Pedagogia, 2024)
This study aims to assess the impact of an experiential learning based training on organic food cultivation in increasing family food security, while also exploring the potential for behavior change and economic resilience. Employing a qualitative research design, the study used case study method. Participants engaged in an experiential learning program designed to impart skills and knowledge in organic food cultivation. Data were collected through interviews, observations, and documentation study, and analyzed using thematic analysis triangulation. The findings highlight the participants' evolving perceptions of the link between organic food cultivation and family food security within the unique urban environment. The training resulted in shifts in consumption patterns and dietary habits within families, fostering healthier choices. Furthermore, the cultivation of organic produce contributed to family finances, reducing expenditure on purchased produce. The study underscores the impact of experiential learning in fostering practical skills and behavior change in an urban community setting. The research contributes to the understanding of how experiential learning interventions can positively influence family food security within specific urban localities. This study suggests that integrating experiential learning approaches into training initiatives can empower urban families to cultivate their own organic produce.